Housing policy reframed?: How conceptual framing affects support for social housing policies in Germany - Schnepf, Julia; Christmann, Ursula; Groeben, Norbert (German politics, 2021)
Housing policy is a growing problem in many countries. Three online experiments were conducted to test framing effects in the context of housing policies in Germany. In experiment 1 (N = 303), urban growth was either described as ‘rural exodus’ or ‘influx’ of the rural population into urban areas. Experiment 2 (N = 300) focused on framing effects in the current expropriation debate in Germany. A reacquisition policy of private housing was either framed as a measure of ‘expropriation’ or ‘repurchase’. In experiment 3 (N = 311), a vacancy taxation was either labelled to ‘punish’ or ‘overcome’ actual problems with housing shortage. A mini meta-analysis across all three studies shows that conceptual framing affects policy support in a consistent way. The data supports our hypotheses that framing has the power to influence mental representations of policy and solutions. Moreover, moderation analyses were conducted to systematically test the influence of political ideology and perceived issue relevance on framing effects. Results indicate that participants’ ideological self-placement partly affects the effectiveness of linguistic framing in some contexts. Thus, the results expand existing knowledge about the effectiveness of political framing, by making visible not only the possibilities but also the boundaries of framing strategies.
Gesehen am 05.07.2021